IMPACT OF THE GEOLOGICAL AND TECTONIC STRUCTURE IN THE CREATION OF QUARRY PRODUCTS (CALCITIC MARBLES) OF TALEA MOUNTAINS (NORTH - CENTRAL CRETE) - Γαλανάκης Δ.; Βιδάκης Μ. (Bulletin of the Geological Society of Greece, 2004)
The Talea mountains (north-central Crete) are consisted of the autochthonous series of the Ionian geotectonic zone. The large recumbert fold of Talea mountain as well as the fracturing of the geological formation are due to an intense folding and thrusting deformation. The marble reserves, in this area, are significant but the geological conditions cause difficulties in their exploitation. The intensive alpine deformation in addition to the intensive karstification of the carbonate rocks resulted to extremely low recovery coefficient